The effectivenessof EM4addition in the biofilter tanks to reduce Total Suspended Solid (TSS) and Ammonia (NH3)content for treating restaurant liquid waste - Yulanda, Febri; Harahap, Sampe; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTRestaurant liquid waste may pollute aquatic environment as ithas high TSS and NH3content.Itshould be processed before being flown to environment.This study aims to understand the effectiveness of EM4 addition in reducing TSS and ammonia content in the restaurant liquid waste. This research was carried out in April 2019 at theNaga Sakti street.A Completely Randomized Design (CRD) was applied with 3 treatments P0 (without EM4), P1 (7,5 ml EM4), P2 (10 ml EM4), P3 (12,5 ml EM4)and 3 replications. Therestaurant liquid waste was kept in the biofilter tank for 6 days (3 days in the anaerob and 3 days in the aerob tanks) and then the TSS and ammonia were analyzed. The best result was obtained in the P2 (10 ml EM4).In that treatment theTSS decreased from 196 mg/L into  63 mg/L and NH3 from 9.08 mg/Linto 4.07 mg/L. The treated liquid waste was then use for rearing Oreochromisniloticus sized 3-5 cm for 96 hours. Thesurvival rate of the fish was 86%.Data obtained shown that theprocessed restaurant liquid waste can be used to rear Oreochromisniloticus. Keyword:Effective Microorganism-4, Anaerob tanks, Aerob tanks, Oreochromisniloticus